Traços autoritários e persuasivos em discursos enunciados pelas forças armadas : ordem do dia - Ramos, Jairo Eduardo Gomes Freitas (2023)
The present work investigates the intonation in written utterances and the construction of meanings under the dialogic bias of Bakhtin and his Circle. To do so, we will analyze the official document of the Brazilian Army, called "Ordem do Dia" in versions of the years 2019, 2020 and 2021. Defense Ministry. 1. Analyze the lexical selection and syntactic organization of utterances in these official documents as carriers of intonations; and 2. Analyze the different versions of the term “democracy” from the time of the 1964 military movement to the present day. Thus, we will be able to discursively describe the orientation marks of the utterance (towards the other). In order to achieve these objectives, we will discuss, based on the theoretical-methodological foundation of the Bakhtin Circle, fundamental concepts of the Circle's thought, such as: valuation, intonation, speech genres, plurilingualism, dialogism, ideology, verbal interaction, in addition to reflecting on the understanding of persuasive and authoritarian meaning effects in discourses in the works of Bakhtin and his Circle. As a result of this research, it was verified that of the three Orders of the Day, it was possible to perceive that they are practically paraphrases of each other, the three have the same meaning, that is, they consider the same topics: threat to democracy, conflicts in Europe, participation of Brazil in World War II, the commitment by the Armed Forces to save Brazilians from the threats of implantation of totalitarian regimes in Brazil and the amnesty. It is practically the same speech paraphrased in the three orders. It was also possible to verify that the typical characteristics of the discourse of the military genre: clear, objective, with practically no approach by the speaker that generates any kind of controversy or dubious meaning in the statements by the interlocutor, in this case the troop. It is a monological speech and, on the part of the speaker, authoritative, which is possible to perceive through the lexical selection and the syntactic structure present in the speech to the troop